GUIDANCE AND COUNSELING SERVICE MANAGEMENT INCLUSIVE HIGH SCHOOL TARBIYATUL ISLAMIYAH BATANGAN PATI - Kholiq, Abdul; Sujito, Sujito; Islah, Islah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Management of Guidance and Counseling Services at Inclusive High School Tarbiyatul Islamiyah Batangan Pati. Inclusive High School Tarbiyatul Islamiyah Batangan Pati is the only madrasa in Batangan sub-district that implements an inclusive education model, the inclusive classroom model is the implementation of teaching and learning activities that accommodate the needs of regular students and students with special needs. From the above background, this study aims to find out: 1) to find out how the implementation of Guidance and Counseling Service Management in Tarbiyatul Islamiyah Inclusive Madrasah Aliyah Batang Pati, 2) to find out what the supporting and inhibiting factors are Guidance and Counseling Service Management in Inclusive Madrasah Aliyah Tarbiyatul Islamiyah Batang Pati. This research is a field research using a qualitative approach, the data collection was obtained using field observation techniques on the management of guidance and counseling services, interviews with the head of madrasah, counseling guidance teachers, special assistant teachers, student representatives, curriculum representatives, public relations officers, madrasah security, subject teachers, students, parents and madrasa alumni. In addition to the primary data, the researchers also used secondary data including student documentation, documentation of guidance and counseling services, and photos of activities, all data were analyzed using data reduction, the main things related to the management of guidance and counseling services, approach models and methods. used in the management of guidance and counseling services, then verification as a conclusion from the analysis. The results showed that: (1) Guidance and Counseling Service Management includes planning, daily service planning, monthly service planning, semester service planning and annual service planning and individual guidance and group guidance planning, organizing includes, the existence of an organizational structure for guidance and counseling services, and division of tasks for guidance and counseling services, actuating includes preventive actions, curative and repressive actions, and evaluations which include monthly evaluations, semester evaluations, annual evaluations and supervision, (2) supporting factors, namely the active role of the foundation, the leadership of the madrasah principal, action fast response counseling guidance teacher. Harmony in the relationship between homeroom teachers and students and communication between counselors and related stakeholders, while the inhibiting factors are the corona virus pandemic, lack of parental response, limited facilities and infrastructure.